Carl Popper's Open Society as a Model for The Development and Progress of Societies - إبراهيم, زانا; إبراهيم رزوق (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research attempts to shed light on the most important intellectual, cognitive and political principles and foundations, and the characteristics and features that characterize the open society accordinsg to the German thinker and philosopher Karl Popper (1902-1944), where the contradiction between the open society and the The closed society and the search for mechanisms of transition from a closed society to an open society according to the study of partial engineering, which is a policy technique that political and social reform is partially based on, in contrast to utopian engineering, which is based on total planning, and it is a holistic tendency that aims to change at once and not step by step as He sees it partial geometry. In addition, the study of rationality, freedom, individualism and egalitarian democracy. Defining the most important features and advantages of the liberal populist open society and its reform mechanism.